The impact of COVID‐19 lockdown on brain metabolism. Issue 2 (12th October 2021) - Guedj, Eric; Campion, Jacques‐Yves; Horowitz, Tatiana; Barthelemy, Fanny; Cammilleri, Serge; Ceccaldi, Mathieu
Abstract: This study aims to evaluate the impact of French national lockdown of 55 days on brain metabolism of patients with neurological disorders. Whole‐brain voxel‐based PET analysis was used to correlate 18 F‐FDG metabolism to the number of days after March 17, 2020 (in 95 patients; mean age: 54.3 years ± 15.7; 59 men), in comparison to the same period in 2019 before the SARS‐CoV‐2 outbreak (in 212 patients; mean age: 59.5 years ± 15.8; 114 men), and to the first 55 days of deconfinement (in 188 patients; mean age: 57.5 years ± 16.5; 93 men). Lockdown duration was negatively correlated to the metabolism of the sensory‐motor cortex with a prevailing effect on the left dominant pyramidal tract and on younger patients, also including the left amygdala, with only partial reversibility after 55 days of deconfinement. Weak overlap was found with the reported pattern of hypometabolism in long COVID (<9%). Restriction of physical activities, and possible related deconditioning, and social isolation may lead to functional disturbances of sensorimotor and emotional brain networks. Of note, this metabolic pattern seems distinct to those reported in long COVID. Further longitudinal studies with longer follow‐up are needed to evaluate clinical consequences and relationships on cognitive and mental health against functional deactivation hypothesis, and to extend these findings to healthy subjects in the context of lockdown. Abstract : Lockdown duration is negatively correlated to the metabolism of the sensory‐motor cortex with a prevailing effect on the left dominant pyramidal tract and on younger patients, also including the left amygdala, with only partial reversibility after 55 days of deconfinement. Weak overlap is found with the reported pattern of hypometabolism in long COVID (<9%). Restriction of physical activities, and possible related deconditioning, and social isolation may lead to functional disturbances of sensorimotor and emotional brain networks.